The anti-angiogenic tyrosine kinase inhibitor Pazopanib kills cancer cells and disrupts endothelial networks in biomimetic three-dimensional renal tumouroids. (May 2020) - Stamati, Katerina; Redondo, Patricia A; Nyga, Agata; Neves, Joana B; Tran, Maxine GB; Emberton, Mark; Cheema, Umber; Loizidou, Marilena
Pazopanib is a tyrosine kinase inhibitor used to treat renal cell carcinoma. Few in vitro studies investigate its effects towards cancer cells or endothelial cells in the presence of cancer. We tested the effect of Pazopanib on renal cell carcinoma cells (CAKI-2, 786-O) in two-dimensional and three-dimensional tumouroids made of dense extracellular matrix, treated in normoxia and hypoxia. Finally, we engineered complex tumouroids with a stromal compartment containing fibroblasts and endothelial cells. Simple CAKI-2 tumouroids were more resistant to Pazopanib than 786-O tumouroids. Under hypoxia, while the more 'resistant' CAKI-2 tumouroids showed no decrease in viability, 786-O tumouroids required higher Pazopanib concentrations to induce cell death. In complex tumouroids, Pazopanib exposure led to a reduction in the overall cell viability (p < 0.0001), disruption of endothelial networks and direct killing of renal cell carcinoma cells. We report a biomimetic multicellular tumouroid for drug testing, suitable for agents whose primary target is not confined to cancer cells.